Glomeruli Sparing Pattern of Unclassified Renal Cell Carcinoma: A Rare Neoplasm - Nagarajan, Deepa; Mallya, Mrinal; Shah, Mita (Annals of Pathology and Laboratory Medicine, 2021)
Unclassified renal cell carcinoma (URCC), an aggressive form of renal cell carcinoma (RCC), represents 0.7– 5 .7% of renal tumours. Glomerular sparing in renal neoplasms (GS) is defined as a unique growth pattern in which tumour cells overrun intact glomeruli. An elderly woman presented with symptoms of left flank pain for three months along with fullness in the abdomen. On clinical and radiological examination, a renal mass was revealed and operated upon. A diagnosis of URCC with a glomerular sparing pattern was made on histopathological examination. The pathological details of this rare neoplasm are presented in this article.